DESEMPENHO AGRONOMICO DE CULTIVARES DE AVEIA NOS ANOS DE CULTIVO NA PRESENÇA E AUSENCIA DE FUNGICIDA - Matter, Edegar; Silva, Adair J. d.; Martins, Luis F. d. S.; Battisti, Gabriel K.; Gaviraghi, Juliano; Antonow, Diovane; Mattioni, Tânia C.; Bandeira, Taiane P.; Krüger, Cleusa A. M. B.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo